PERANCANGAN SISTEM KONTROL TORSI PADA MOTOR INDUKSI 3 FASA DENGAN UMPAN BALIK NONLINIER - Setiawan, Dany
Abstract: Recently, induction motor is widely used in industry because of its advantages compared with direct current motor. The advantages of induction motor is low cost in operation and maintenance, compact, etc. However, beside of its advantages, induction motor is difficult to be controlled because of its non linearity and coupling problem between flux producing current and torque producing current components. By the vector control technique and the advanced of power electronics, the coupling prcblem in induction motor can be overcome so induction motor can be controlled easily as direct current motor. Linierization method then used to obtain controller for nonlinier system, thus make it possible to design a nonlinier state feedback to controlling system as often performed in tinier system. From the simulation result of torque controlling and rotor magnetizing current controlling in three phase induction motor (5 Hp, 1 pole pairs, 60 Hz, 208 V, 21 A) using P and P+D, it is observed that induction motor can reach set-point for torque and rotor magnetizing current with both overshoot 0%. In addition, the change of rotor resistance (Rr) parameter to 0.115 S2 (6.5 %) and magnetizing inductance (Lm) parameter to 0.044 H (2 %) are not influenced the designed controlling, or in other words are not sensitive to the change of parameter.